Addressing Mental Health Challenges in Nepal: A Review of Policies, Status, and Strategies for Improvement - Prajapati, Rama; Lamichhane, Aarju; Shrestha, Bhanu; Shah, Lata Kusum; Siddique, Mariyam; Singh, Pankaj Kumar; Bhattarai, Stuti; Manandhar, Sujina; Giri, Suja (Journal of Multidisciplinary Research Advancements, 2024)
Mental health is a crucial aspect of overall well-being, encompassing an individual’s emotional, psychological, and social well-being. In Nepal, mental health issues are a significant concern, with challenges related to governance, policy implementation, and service delivery. This review examines the mental health status in Nepal, analyzes existing policies, and proposes strategies for improvement. Databases, including ScienceDirect, Springer, NepJol, PubMed, and Google Scholar, were searched to gather relevant literature. The review identified key challenges in Nepal’s mental health system, including the lack of a revised and fully implemented mental health policy, discriminatory provisions in the legislation, inadequate planning and funding at the district level, and limited workforce and resources. Despite positive developments, such as including mental health in general health policies and NGO involvement, significant barriers remain. To improve mental health in Nepal, it is essential to implement public policies favoring mental health, train individuals in personal skills, promote healthy lifestyles, and intervene through community actions. These strategies aim to create supportive environments and increase awareness of mental health issues, ultimately improving the population’s overall well-being.